2005
DOI: 10.1021/ma0474628
|View full text |Cite
|
Sign up to set email alerts
|

N-Methylpyrrole-Terminated Polyisobutylene through End-Quenching of Quasiliving Carbocationic Polymerization

Abstract: Quasiliving isobutylene polymerization initiated by 2-chloro-2,4,4-trimethylpentane/TiCl4/2,6-dimethylpyridine in 60/40 n-hexane/methyl chloride at −70 °C was allowed to reach 98+% monomer conversion and then reacted with N-methylpyrrole. All polyisobutylene (PIB) chains alkylated the N-methylpyrrole ring to form a mixture of 46% 2-PIB−N-methylpyrrole and 54% 3-PIB−N-methylpyrrole. GPC indicated the absence of coupled PIB, confirming that exclusively monosubstitution had occurred. Complete 1H and 13C NMR chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 19 publications
5
48
0
Order By: Relevance
“…26 In addition, we have demonstrated that the N-alkyl group can be exploited as an alkylene tether for the attachment of more useful functional groups to PIB, such as primary halogen. 27 Herein, we report the in situ functionalization of PIB with pyrroles bearing a protected hydroxyl group attached via an N-alkylene tether as a means for single-pot synthesis of primary hydroxyfunctional PIB (Scheme 1).…”
Section: Introductionmentioning
confidence: 96%
“…26 In addition, we have demonstrated that the N-alkyl group can be exploited as an alkylene tether for the attachment of more useful functional groups to PIB, such as primary halogen. 27 Herein, we report the in situ functionalization of PIB with pyrroles bearing a protected hydroxyl group attached via an N-alkylene tether as a means for single-pot synthesis of primary hydroxyfunctional PIB (Scheme 1).…”
Section: Introductionmentioning
confidence: 96%
“…Molecular weights and polydispersities (PDIs) of polymers were determined using a SEC system consisting of a Waters Alliance 2690 Separations Module, an on-line multi-angle laser light scattering (MALLS) detector (MiniDAWN TM , Wyatt Technology Inc.) and an interferometric refractometer (Optilab DSP TM , Wyatt Technology Inc.), as previously described (20). Freshly distilled THF served as the mobile phase and was delivered at a flow rate of 1.0 mL/min.…”
Section: Instrumentationmentioning
confidence: 99%
“…Friedel–Crafts alkylation could be useful for polymer reactions in cationic polymerizations because an aromatic ring reacts with an electrophile or an electron‐deficient species. For example, the use of the electrophilic reactions of aromatic groups has been examined as a novel synthetic tool for producing star‐shaped polymers, hyperbranched polymers or end‐functional polymers via the cationic polymerization of isobutylene or vinyl ethers . More reactive aromatic rings such as a naphthyl group could allow more facile synthesis of well‐defined polymers in cationic polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve an efficient reaction of living propagating cations with naphthalene rings, the propagating cations should have high reactivity, which allows the use of less reactive monomers for the synthesis. Highly reactive polyisobutylene or polystyrene carbocations were employed in the aforementioned synthesis using the Friedel–Crafts reaction . Another candidate for such less reactive monomers generating highly reactive species is p ‐acetoxystyrene (AcOSt).…”
Section: Introductionmentioning
confidence: 99%